Quantum sensing the brain. (May 2021) - Coleman, Hannah; Brookes, Matt
Abstract : Novel technology in healthcare based on fundamental physics saves millions of lives every year but while these machines have revolutionized medicine, the next generation must meet even greater challenges. Hannah Coleman and Matt Brookes are hoping that the University of Nottingham's new quantum-enabled MEG scanner will herald a new dawn in the study of human brain function